2019
DOI: 10.1371/journal.pone.0222145
|View full text |Cite|
|
Sign up to set email alerts
|

Habitat disturbance and the organization of bacterial communities in Neotropical hematophagous arthropods

Abstract: The microbiome plays a key role in the biology, ecology and evolution of arthropod vectors of human pathogens. Vector-bacterial interactions could alter disease transmission dynamics through modulating pathogen replication and/or vector fitness. Nonetheless, our understanding of the factors shaping the bacterial community in arthropod vectors is incomplete. Using large-scale 16S amplicon sequencing, we examine how habitat disturbance structures the bacterial assemblages of field-collected whole-body hematophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 89 publications
(109 reference statements)
1
4
0
Order By: Relevance
“…aegypti communities. Such interactions remain largely unexplored but should be considered, as habitat disturbance can alter the microbiome and thus affect adult vector phenotypic traits [55]. In agreement with other studies, we found that the predominant microbiota at Ae.…”
Section: Discussionsupporting
confidence: 91%
“…aegypti communities. Such interactions remain largely unexplored but should be considered, as habitat disturbance can alter the microbiome and thus affect adult vector phenotypic traits [55]. In agreement with other studies, we found that the predominant microbiota at Ae.…”
Section: Discussionsupporting
confidence: 91%
“…To date, few studies have compared the microbiomes of multiple tick species collected from the same geographic region. Most comparative microbiome studies focused on Ixodes scapularis and one other tick species (30, 32, 35, 50, 52) or considered only three species (56,57). Nakao et al (33) found evidence for species-specific effects on the microbiome composition of seven tick species.…”
Section: Discussionmentioning
confidence: 99%
“…The differences found in the physicochemical parameters of breeding sites raise questions about their possible impact on the structure and composition of A. aegypti communities. Such interactions remain largely unexplored but should be considered, as habitat disturbance can alter the microbiota and thus affect adult vector phenotypic traits [59].…”
Section: Discussionmentioning
confidence: 99%